Populasi Tungau Parasit Varroa jacobsoni: Penyebab Kematian Pupa dan Korelasinya terhadap Produksi Madu Apis cerana pada Sisiran Sarang Membujur dan Melintang - Hery Pratiknyo; Darsono Darsono (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2012)
Bee keeping of local bee (Apis cerana Fab.) in Purbalingga Regency is spread widely from  25 m to 350 m asl, eventhough quatatively the production is still low. It is caused by parasitic mite attack,  Varroa jacobsoni. This mite attack then suck haemolymph of the pupae,  meanwhile if the bee comb cell  consist of more than one mites, the pupae will die, consequently the honey production will decrease. The aims of the research are: 1) to know a mount of individual mite living and caused the death of one bee pupae, .2) to define the correlationship between density of parasitic mite and honey production, 3). To differ parasite mite V. jacobsoni  density in longitudinal and cross posision of combs.  Method used was survey with purposive random sampling tehnique on two posision of bee comb, 15 samples were taken in each posision.  The data were analyzed  by counting the amount of mite living on every dead pupae and the correlation was analyzed for the relationship between relative density of parasite mite and  honey production. The result shows that correlation between relative density of parasitic mite and honey production is unsignificant. Conclusion of the research are: 1) amount of  parasitic mite living on bee pupae and causing death is 5,80 individual on cross posisition comb and 4,71 individual on longitudinal posision comb. 2) correlation between relative density of parasitic mite and honey production is unsignificant. 3). The relative density of parasitic mite between two posisions of comb is unsignificant.